Comparison of active and passive targeting of doxorubicin for somatostatin receptor 2 positive tumor models by octreotide-modified HPMA copolymer-doxorubicin conjugates. (2nd January 2016) - He, Shuang; Zhou, Zhou; Li, Lian; Yang, Qingqing; Yang, Yang; Guan, Shan; Zhang, Jian; Zhu, Xi; Jin, Yun; Huang, Yuan
Abstract: Somatostatin receptor 2 (SSTR2), specifically over-expressed on many tumor cells, is a potential receipt for active targeting in cancer therapy. In the present study, octreotide (Oct), which had high affinity to SSTR2, was attached to N -(2-hydroxypropyl) methacrylamide (HPMA) polymeric system to enhance the antitumor efficiency of the anticancer drug doxorubicin (DOX). Two kinds of cell lines (HepG2 and A549), which overexpress SSTR2, were chosen as cell models. Compared with non-modified conjugates, Oct-modified conjugates exhibited superior cytotoxicity and intracellular uptake on both HepG2 and A549 cell lines. This might be due to the mechanism of receptor-mediated endocytosis. Subsequently, the in vivo biodistribution and antitumor activity evaluations showed that Oct modification significantly improved the tumor accumulation and antitumor efficacy of HPMA copolymer conjugates in SSTR2 over-expressed Kunming mice bearing H22 tumor xenografts. In summary, Oct-modified HPMA polymer-DOX conjugates might be a promising system for the treatment of SSTR2 over-expressed cancers.